Pharmacological classes that extend lifespan of Caenorhabditis elegans - Carretero, Maria; Gomez-Amaro, Rafael L.; Petrascheck, Michael (Frontiers in Genetics, 2015)
Recent progress in the field of aging has resulted in ever increasing numbers of compounds that extend lifespan in C. elegans. Lifespan extending compounds include metabolites and synthetic compounds, as well as natural products. For many of these compounds, mammalian pharmacology is known, and for some the actual targets have been experimentally identified. In this review, we explore the data available in C. elegans to provide an overview of which pharmacological classes have potential for identification of further compounds that extend lifespan.